Otolaryngology head & neck surgery - Cummings, Charles W. (St. Louis : Mosby, 1999)
All five volumes of the latest edition of the leading reference in otolaryngology-head and neck surgery are available on a state of the art CD-ROM. It is easy to use and allows rapid access to information when time is critical
System requirements: Windows ; 486 or Pentium-based PC, running Windows 95, Windows NT, or Windows 3.1 (Windows 3.1 requires installed TCP/IP stack and configured modem) ; 16 MB or RAM minimum ; 30 MB free hard disk space minimum ; 2X or faster CD-ROM drive ; 640 x 480 color monitor with thousands of colors or better ; 28.8 or faster modem (optional for Internet access)
Keywords: Otorhinolaryngologic diseases -- surgery